Pemberdayaan Masyarakat Desa Galuga melalui Implementasi Artificial Intelligence untuk Pemilahan Sampah Otomatis - Suyatno Suyatno; Yus Natali; Hesmi Aria Yanti; Ade Nurhayati; Alva Nurvina Sularso (Universitas Negeri Gorontalo, 2026)
Solid waste management in Galuga Village is still largely dependent on manual sorting practices, resulting in low sorting efficiency and limited community participation. This community service program aims to support source-level waste segregation through the implementation of an Artificial Intelligence (AI)–based automatic waste sorting system that can be operated independently by the community. The activity was conducted using a Participatory Action Research (PAR) approach, emphasizing active community involvement in the design, utilization, and evaluation of the system. The implementation results indicate that the developed AI system achieved a highest validation accuracy of 93.37%, enabling faster and more consistent waste sorting compared to manual methods. Furthermore, observations and questionnaire results from the initial pilot implementation show improved community understanding and acceptance of waste segregation practices, as well as increased readiness to adopt the system in daily activities. These findings suggest that integrating AI technology with a participatory approach has the potential to enhance the effectiveness of community-based waste management and may be further developed as a sustainable technology empowerment model at the village level.